Use of ultraportable vacuum therapy systems in the treatment of venous leg ulcer - Cuomo, Roberto; Nisi, Giuseppe; Grimaldi, Luca; Brandi, Cesare; D'Aniello, Carlo (Acta Biomedica Atenei Parmensis, 2017)
Background: The high incidence of venous leg ulcers and the difficult to give a complete healing involves in an increase of costs for National Health System. Main therapies to obtain a fast healing are compressive bandages, treatment of abnormal venous flow and in-situ-strategies of wound care. Negative pressure therapy does not conventionally used, because these systems not allow the use of compression bandages. Recently the development of ultraportable devices has improved the compliance and the results. Methods: Ten patients with venous chronic ulcer on the lower extremities were recruited for this study: all patients had venous leg ulcers from at least one year. We treated the patients with autologous partial thickness skin graft and subsequently we applied NANOVA device included in compressive bandage. We used NANOVA for fourteen days and after we made traditional medications. We submitted a questionnaire to evaluate the impact of dressing and NANOVA device in the quality of life of patients. Results: The device contributed to the formation of granulation tissue and increased the success rate of autologous skin graft without limiting mobility of patient. In addition to this, we have been able to perform compression bandages thanks to small size of this device. Eight ulcers healed within 90 days of medication. Conclusions: We believe that ultraportable negative pressure systems are useful devices for treatment of venous leg ulcers because them allows to realize a compressive bandage without mobility limitations.